2021
DOI: 10.1038/s41598-020-79552-z
|View full text |Cite
|
Sign up to set email alerts
|

Host mitochondrial transcriptome response to SARS-CoV-2 in multiple cell models and clinical samples

Abstract: SARS-CoV-2 induces a muted innate immune response compared to other respiratory viruses. Mitochondrial dynamics might partially mediate this effect of SARS-CoV-2 on innate immunity. Polypeptides encoded by open reading frames of SARS-CoV and SARS-CoV-2 have been shown to localize to mitochondria and disrupt Mitochondrial Antiviral Signaling (MAVS) protein signaling. Therefore, we hypothesized that SARS-CoV-2 would distinctly regulate the mitochondrial transcriptome. We analyzed multiple publicly available RNAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 36 publications
10
69
0
1
Order By: Relevance
“…Translation inhibition by SARS-CoV-2 Nsp1 via the blocking of mRNA access to ribosomes has been reported previously [ 61 , 62 ]. SARS-CoV-2 infection-induced down-regulation of genes associated with cellular respiration and mitochondrial function has also been shown in human lungs [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Translation inhibition by SARS-CoV-2 Nsp1 via the blocking of mRNA access to ribosomes has been reported previously [ 61 , 62 ]. SARS-CoV-2 infection-induced down-regulation of genes associated with cellular respiration and mitochondrial function has also been shown in human lungs [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of SARS-CoV-2, it has been hypothesized that viral protein ORF9b would suppress MAVS downstream signaling (through Tumor necrosis actor Receptor-Associated Factor (TRAF)3 and TRAF6) and thereby the innate immunity and the related release of interferons could lose robustness [190]. In accordance with this prediction, it has been recently demonstrated that ORF9b from SARS-CoV-2 colocalizes on mitochondria and interacts with TOM70 protein in the outer membrane to suppresses IFN-I responses [203], and ORF9c interacts with complex I of the respiratory chain [204]. ORF9b may promote virus replication by inhibiting the apoptotic destruction of infected cells and by supporting their survival and viability through induction of mitochondrial elongation and fusion.…”
Section: Mitochondrial Disruption Aggravating Covid-19mentioning
confidence: 70%
“…Prior research in our lab and others has demonstrated positive effects of large, immersive 3D video game playing on hippocampal-based memory ability (Clemenson and Stark, 2015 ; Clemenson et al, 2019 , 2020 ; Wais et al, 2021 ). For example, in an intervention using young non-gamer adults, we found that 2 weeks of playing Super Mario 3D World improved hippocampal-based memory performance relative to both active and no-contact control groups (Clemenson and Stark, 2015 ), with the amount of exploration in the game correlating with the amount of improvement.…”
Section: Introductionmentioning
confidence: 78%
“…The present study sought to determine whether playing Minecraft would improve memory function in middle-aged adults in the way it has improved memory function in younger adults (Clemenson et al, 2019 ) and in the way other video games centered on exploration and with large amounts of novelty have improved memory ability in both younger (Clemenson and Stark, 2015 ) and older (Clemenson et al, 2020 ; Wais et al, 2021 ) adults. The results were remarkably consistent with our prior work ( Figure 3 ) and the work of others (Wais et al, 2021 ). Even modest amounts of gameplay (e.g., 30 min/day over 2–4 weeks) improved performance on a hippocampal dependent memory task while not affecting a simpler recognition memory task that is far less reliant upon the hippocampus.…”
Section: Discussionmentioning
confidence: 99%